Enhancing egg production and quality by the supplementation of probiotic strains (Clostridium and Brevibacillus) via improved amino acid digestibility, intestinal health, immune response, and antioxidant activity - Obianwuna, Uchechukwu Edna; Qiu, Kai; Chang, Xin-yu; Zhang, Hai-jun; Wang, Jing; Qi, Guang-hai; Sun, Tie-hu; Su, Yong-bo; Wu, Shu-geng (Frontiers in Microbiology, 2022)
This study focused on evaluating the influence of Clostridium butyricum and Brevibacillus strains on the egg production, egg quality, immune response and antioxidant function, apparent faecal amino acid digestibility, and jejunal morphology, when supplemented as probiotics in the diets of laying hens in peak-phase. A total of 288 healthy 30-weeks old Hy-Line Brown laying hens were arbitrarily assigned to four dietary groups which included control diet, control diet supplemented with 0.02% C. butyricum zlc-17, C. butyricum lwc-13 or Brevibacillus zlb-z1 respectively, for 84 days. Results showed that dietary C. butyricum and Brevibacillus sp exerted positive significant influence (P ≤ 0.05) compared to the control group on the performance, egg quality and physiological response of the birds. The diets could reduce mortality rate, enhance (P ≤ 0.05) egg weight and egg mass, egg production rate and feed efficiency. Further analysis suggested that the probiotic strains can enhance (P ≤ 0.05) egg shell quality, Haugh unit, thick albumen content and albumen height. Also, probiotics enhanced (P ≤ 0.05) antioxidant status via increased antioxidant enzymes and jejunal morphology as evidenced by increased villi surface area, ratio of villi height to crypt depth, villi width, villi height and a significant reduction in crypt depth. Besides, nutrient absorption and retention was enhanced, as apparent faecal amino acid digestibility of key essential amino acids was substantially improved in the diet-based group. The concentrations of immunoglobulin M and A (IgM and IgA) increased significantly (P ≤ 0.05) in the probiotics group and same effect was notable for complement proteins (C3) and immune organ (Spleen). Conclusively, supplementation of Clostridium butyricum zlc-17 in comparison to Clostridium butyricum lwc-13 and Brevibacillus zlb-z1 strains significantly (P ≤ 0.05) promoted antioxidant status, modulated intestinal structure, enhanced amino acid digestibility and regulated the immunity index of the laying hens which finally improves the laying performance and egg quality of the laying hens. Key Words: Probiotics; Laying hens; Egg Quality; Gut Health; Immune and Antioxidant Function.